Method for manufacturing a zinc-manganese dioxide battery, set for manufacturing a zinc-manganese dioxide battery, and battery produced thereby

JP2024514940A5Pending Publication Date: 2025-03-26VARTA MICROBATTERY GMBH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023564422
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-21
Filing Date
2022-04-21
Publication Date
2025-03-26

AI Technical Summary

Technical Problem

Conventional printed electrochemical cells, particularly those using zinc-manganese dioxide, have limited capacity and current carrying ability, making them unsuitable for energy-intensive applications like LTE mobile radio chips, and pose environmental and safety concerns.

Method used

A method for manufacturing zinc-manganese dioxide batteries involving the application of pastes containing zinc powder, manganese dioxide, and a chloride-containing electrolyte with mineral particles to form a boundary layer between electrodes and separators, enhancing electrical conductivity and safety.

Benefits of technology

The method produces batteries capable of delivering high current pulses suitable for LTE mobile radio chips, ensuring safety and environmental compatibility while maintaining low production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To produce a zinc-manganese dioxide battery, a first and a second electrical conductor are applied onto an electrically non-conductive substrate. A layered negative electrode and a layered positive electrode are formed from a paste onto the electrical conductor, and then at least one electrolyte layer is applied onto the negative electrode and / or onto the positive electrode and / or onto the layered separator. A stack of layers with a continuous electrode / separator / positive electrode is then formed. In addition to the active material and the electrode binder, each electrode paste contains a solvent and / or a dispersant. The paste for producing at least one electrolyte layer contains, in addition to at least one water-soluble chloride-containing salt, mineral particles, and a solvent and / or a dispersant, the proportion of mineral particles in the paste being at least 5% by weight and at most 60% by weight. It can be supplied in a set with the electrode paste. In the finished battery, the mineral particles are located at the connection between the electrode and the separator and form a boundary layer permeable to the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention described below relates to a method for producing a zinc-manganese dioxide battery and a set for producing a zinc-manganese dioxide battery. Furthermore, the invention relates to a battery produced according to the method and a battery produced using the set. [Background technology]

[0002] An electrochemical cell necessarily comprises a positive and a negative electrode. When an electrochemical cell is discharged, an energy-producing chemical reaction takes place, which is composed of two electrically coupled but spatially separated partial reactions. One partial reaction, which takes place at a relatively lower redox potential, takes place at the negative electrode, and one at a relatively higher redox potential takes place at the positive electrode. During discharge, electrons are released as a result of an oxidation process at the negative electrode, which leads to a flow of electrons - usually via an external load - to the positive electrode, from which a corresponding amount of electrons is absorbed. Thus, a reduction process takes place at the positive electrode. At the same time, an ionic current corresponding to the electrode reaction is generated in the battery. This ionic current is ensured by an ion-conducting electrolyte. In secondary electrochemical cells, this discharge reaction is reversible, i.e. it is possible to reverse the conversion of chemical energy into electrical energy that took place during discharge. On the other hand, in primary batteries, the discharge reaction is irreversible or the battery cannot be recharged for other reasons.

[0003] The term "battery" originally meant several electrochemical cells connected in series, and this is how it is used in the context of this application.

[0004] Electrochemical cells can not only be produced by assembling solid individual components. In recent years, batteries in which at least the individual functional components, in particular the electrodes and / or the required conductor tracks, are produced by printing, i.e. from pastes containing solvents and / or suspending agents, have become increasingly important. Batteries produced in this way are known, for example, from WO 2006 / 105966 A1.

[0005] Generally, a printed electrochemical cell has a multi-layer structure. In a conventional design, a printed electrochemical cell generally comprises two current collector layers, two electrode layers, and an electrolyte layer in a stacked arrangement. The electrolyte layer is disposed between the two electrode layers, while the current collectors form the upper and lower parts of the electrochemical cell, respectively. An electrochemical cell having such a structure is described, for example, in U.S. Pat. No. 4,119,770.

[0006] In contrast, the above-mentioned WO 2006 / 105966 A1 describes a much flatter electrochemical cell in which the electrodes are located next to each other (coplanar arrangement) on a flat, electrically non-conductive substrate. The electrodes are connected via an ionically conductive electrolyte, which can be, for example, a gelled zinc chloride paste. The electrolyte is generally reinforced and stabilized by a non-woven or mesh-like material.

[0007] Although conventional printed batteries such as those described in WO 2006 / 105966 A1 are suitable for many applications, they have a very limited current carrying capacity, especially for pulsed loads. For example, mobile phone chips impose excessively high demands on traditional printed batteries in terms of their energy consumption. This is especially true for the newer generation of mobile radio chips transmitting according to the LTE standard (LTE = Long Term Evolution). Depending on the selected radio protocol, peak currents of up to 400 mA must be available at least over a short time window. For versatility, printed batteries must be as cheap to produce as possible. In addition, environmental compatibility and safety are important parameters for all products used in large quantities. Summary of the Invention [Problem to be solved by the invention]

[0008] The object of the present invention was to provide a battery that is safe, can be produced at low cost, is environmentally compatible, in particular does not create problems regarding its disposal, and is also able to meet the requirements of energy-intensive applications such as mobile radio chips, in particular mobile radio chips operating according to the LTE standard. [Means for solving the problem]

[0009] To solve this problem, the invention proposes a method for producing a zinc-manganese dioxide battery having the features of claim 1 and a set for producing a zinc-manganese dioxide battery having the features of claim 7. A battery having the features of claim 9 is also an object of the invention. Further developments of the invention are the subject of the subclaims.

[0010] The method according to the present invention The method according to the invention necessarily comprises the following steps a. to e.: a. applying a first electrical conductor to an electrically non-conductive substrate and a second electrical conductor to an electrically non-conductive substrate; b. applying a layered negative electrode directly to a first electrical conductor and a layered positive electrode directly to a second electrical conductor; c. providing a layered separator; d. applying at least one electrolyte layer to the layered negative electrode, and / or to the layered positive electrode, and / or to the separator; and e. Forming a stack of layers having a continuous anode / separator / cathode. To apply the electrodes and at least one electrolyte layer, a paste is used that is defined as follows: f. The paste for making the negative electrode comprises the following components: - Zinc powder (mercury free) - Electrode binder - Solvents and / or dispersants g. The paste for making the positive electrode contains the following components: - Manganese dioxide - Conductive materials to improve electrical conductivity - Electrode binder - Solvents and / or dispersants h. A paste for producing at least one electrolyte layer comprising the following components: at least one water-soluble chloride-containing salt, preferably zinc chloride and / or ammonium chloride; - Mineral particles - Solvents and / or dispersants

[0011] It should be particularly emphasized that according to the invention, the proportion of mineral particles in the paste is at least 5% by weight and at most 60% by weight. What is more preferred is that the minimum proportion of mineral particles is at least 10% by weight, preferably more than 10% by weight, and the maximum proportion is at most 50% by weight, preferably at most 40% by weight.

[0012] The percentages given here refer to the total weight of the paste, i.e. the weight of all components of the paste including solvents and / or dispersants, which applies below for all percentages relating to mass fractions of paste components.

[0013] Advantages of the Invention To transmit an LTE message, first a scanning process is performed. During this process, the label searches for possible frequencies for data transmission. This process takes an average of 2 s and requires 50 mA. When a frequency is found, a so-called TX pulse is transmitted. Such a pulse lasts about 150 ms and requires a current pulse of about 200 mA. A pulse with a length of 150 ms corresponds approximately to a frequency of 4 Hz. Therefore, the impedance of the battery according to the invention at 4 Hz is important for the transmission of such a pulse.

[0014] The batteries produced according to the method described here give particularly good results in this respect. The mechanism giving rise to the good values ​​has not yet been conclusively elucidated. However, it is suspected that the proportion of mineral particles in the paste used to produce at least one electrolyte layer plays a role here. As will be explained later, these form the boundary layer between the electrodes and the separator. At least one water-soluble chloride-containing salt, in particular zinc chloride and / or ammonium chloride, dissolved in a solvent and / or dispersant then constitutes the actual electrolyte that can penetrate the separator and the boundary layer.

[0015] It is already known in principle, for example from EP 2 561 564 B1, to print the electrolyte with the addition of mineral particles. However, the particles have so far been used as a substitute for the separator, whereas in this case they are used in addition to the separator. It is believed that the boundary layer improves the permeability of the separator for the electrolyte, since it creates a pore gradient and the pores of the separator are not blocked by the particles of the electrode paste. The reasons for the good impedance values ​​are the subject of ongoing research.

[0016] The choice of electrochemical systems with zinc-based negative electrodes is primarily driven by the required safety: systems with zinc-based negative electrodes require aqueous electrolytes and are therefore non-flammable, in addition, zinc is environmentally friendly and inexpensive.

[0017] Preferred separator In particularly preferred embodiments, the separator used has at least one of the following additional features a. to d: a. The separator is a porous plastic film or a porous nonwoven fabric; b. The separator has a thickness in the range of 60 to 120 μm. c. The separator has a porosity (ratio of void volume to total volume) in the range of 35 to 60%. d. The separator is made of a polyolefin, such as polyethylene. Preferably, the immediately preceding features a to c are implemented in combination. In a further preferred embodiment, features a to d are implemented in combination.

[0018] Paste for the production of at least one electrolyte layer In a particularly preferred embodiment, the paste for producing at least one electrolyte layer is characterized by at least one of the following additional features a. to i: a. the mineral particles are selected from the group consisting of ceramic particles, salt particles that are nearly or completely insoluble in water, glass particles, and particles of natural minerals and rocks such as basalt. b.CaCO3 particles are used as the mineral particles. c. The mineral particles have a d50 value in the range of 0.8 μm to 40 μm, preferably in the range of 0.8 μm to 15 μm, particularly preferably in the range of 1.0 μm to 5 μm. d. The paste for producing at least one electrolyte layer is substantially free of mineral particles having a particle size of >80 μm, preferably >60 μm, particularly preferably >45 μm. e. the paste for producing at least one electrolyte layer comprises at least one additive, in particular for adjusting its viscosity, preferably in a proportion within the range of 1 to 8% by weight. f. As an additive for adjusting viscosity, the paste contains a mineral powder having an average particle size (d50) of <500 nm, preferably <200 nm. g. Water is used as a solvent and / or dispersant. h. The proportion of at least one water-soluble chloride-containing salt, in particular zinc chloride and / or ammonium chloride, in the paste is at least 25% by weight and at most 50% by weight. i. the paste for producing at least one electrolyte layer comprises the following components in the following proportions: at least one water-soluble chloride-containing salt, in particular zinc chloride and / or ammonium chloride, from 30 to 40% by weight; - Additive for viscosity adjustment, 2-4% by weight - Mineral particles, 10-30% by weight - Solvents and / or dispersants, 40-55% by weight The paste contains the ingredients, the percentages of which total 100% by weight.

[0019] Preferably, the immediately preceding features a, c and d are implemented in combination. In a further preferred embodiment, features e and f are implemented in combination. Particularly preferably, the immediately preceding features b to i are implemented in combination.

[0020] The term "ceramic particles" is intended to include all particles that can be used to produce ceramic products, including silicate materials such as aluminum silicate, clay minerals, oxide materials such as silicon oxide, titanium dioxide, and aluminum oxide, and non-oxide materials such as silicon carbide or silicon nitride.

[0021] In the context of the present application, the term "virtually or completely insoluble" means that there is at most a low solubility, preferably none at all, in the corresponding solvent at room temperature. In particular, the solubility of the particles that can be used according to the invention of the above-mentioned salts that are virtually or completely insoluble in water should ideally not exceed the solubility of the particularly preferred calcium carbonate in water at room temperature.

[0022] In principle, alkaline electrolytes, such as sodium hydroxide or potassium hydroxide solutions, would also be well suited for the battery according to the invention. However, aqueous electrolytes with a pH in the neutral region have the advantage that they are less dangerous in the event of mechanical damage to the battery. Thus, zinc chloride and ammonium chloride are particularly suitable as chloride-based conductive salts. The pH of the aqueous electrolyte is preferably in the neutral or slightly acidic region.

[0023] Particularly preferably, the mineral particles are CaCO3 particles having a d50 value in the range of 1.0 μm to 5 μm, and the paste for producing at least one electrolyte layer is substantially free of mineral particles having a particle size of >45 μm. The term "substantially free" in this context is further intended to mean that less than 5%, preferably less than 1%, of the mineral particles have a particle size of >45 μm. Furthermore, it is particularly preferred that the mineral particles are contained in the paste for producing at least one electrolyte layer in a proportion of 10 to 20% by weight.

[0024] The mineral powder is preferably silicon dioxide, in particular amorphous silicon dioxide, having an average particle size (d50) of <500nm, preferably <200nm. Particularly preferably, the mineral powder is amorphous silicon dioxide or another mineral powder having an average particle size (d50) of <100nm, more preferably <50nm. Binders such as carboxymethylcellulose can also be used as additives to adjust viscosity.

[0025] It should be noted that the terms solvent and / or dispersant refer to the fact that the paste according to the claimed invention contains or may contain water soluble and water insoluble components, where the water soluble components are present in dissolved form, while the water insoluble components are present in dispersed form.

[0026] Paste for the production of negative electrodes In particularly preferred embodiments, the paste used to produce the negative electrode is characterized by at least one of the following additional features a. to h: a. The paste for preparing the negative electrode contains zinc powder in a proportion of at least 50% by weight, and preferably at least 60% by weight. b. The zinc powder is characterized by a d50 value in the range of 20 μm to 40 μm, and preferably by a particle content of >45 μm of less than 5 wt.%. c. The paste for producing the negative electrode contains at least one additive, in particular for adjusting its viscosity, preferably in a proportion within the range of 1 to 8% by weight. d. The paste contains carboxymethyl cellulose as an additive to adjust viscosity. e. The paste for preparing the negative electrode contains an electrode binder in a proportion of at least 1% by weight, and preferably at most 10% by weight. f. The paste for producing the negative electrode comprises as an electrode binder an electrode binder having elastic properties, in particular an electrode binder from the group comprising polyacrylate (PA), polyacrylic acid (PAA), polychlorotrifluoroethylene (PCTFE), polyhexafluoropropylene (PHFP), polyimide (PI), polytetrafluoroethylene (PTFE), polytrifluoroethylene (PTrFE), polyvinyl alcohol (PVA), polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), and mixtures of the above-mentioned materials. g. Water is used as a solvent and / or dispersant. h. The paste for preparing the negative electrode contains the following components in the following proportions: - Zinc powder (mercury-free), 65-79% by weight - Additive for viscosity adjustment, 1-5% by weight - Binder, elastic (e.g. SBR), 5-10% by weight - solvents and / or dispersants, 15-20% by weight The paste contains the ingredients, the percentages of which total 100% by weight.

[0027] Preferably, the immediately preceding features a. to c. and e. to g. are realized in combination. In a further preferred embodiment, features c. and d. are realized in combination. Particularly preferably, the immediately preceding features a. to h. are realized in combination. Particularly preferably, the electrode binder in the negative electrode is SBR.

[0028] As an alternative to the preferably used carboxymethylcellulose, the mineral powders described above for the electrolyte pastes, having an average particle size (d50) of <500 nm, preferably <200 nm, in particular the amorphous silicon dioxide mentioned above, could also be used as additives for adjusting the viscosity of the paste for the negative electrode.

[0029] Paste for preparation of positive electrode In particularly preferred embodiments, the paste used to produce the positive electrode is characterized by at least one of the following additional features a. to j: a. The paste for preparing the positive electrode contains manganese dioxide in a proportion of at least 50% by weight, and preferably at least 60% by weight. b. The manganese dioxide is present in particulate form and is characterized by a d50 value in the range of 20 μm to 50 μm and preferably by a proportion of particles >55 μm of less than 5% by weight. c. the paste for producing the positive electrode contains at least one additive, in particular for adjusting its viscosity, preferably in a proportion ranging from 1 to 10% by weight; d. The paste contains carboxymethyl cellulose as an additive to adjust viscosity. e. The paste for the preparation of the positive electrode contains an electrode binder in a proportion of at least 5% by weight, and preferably at most 15% by weight. f. The paste for producing the positive electrode comprises as an electrode binder an electrode binder having elastic properties, in particular an electrode binder from the group comprising polyacrylate (PA), polyacrylic acid (PAA), polychlorotrifluoroethylene (PCTFE), polyhexafluoropropylene (PHFP), polyimide (PI), polytetrafluoroethylene (PTFE), polytrifluoroethylene (PTrFE), polyvinyl alcohol (PVA), polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), and mixtures of the above-mentioned materials. g. The paste for preparing the positive electrode contains a conductive material in an amount of 3% by weight to 10% by weight. h. The positive electrode fabrication paste contains at least one conductive material selected from the group consisting of activated carbon, activated carbon fiber, carbide-derived carbon, carbon aerogel, graphite, graphene, and carbon nanotubes (CNTs). i. Water is used as a solvent and / or dispersant. j. The paste for preparing the positive electrode contains the following components in the following proportions: - Manganese dioxide, 50-70% by weight - conductive materials (e.g. graphite, carbon black), 3-30% by weight - Viscosity adjusting additive, 2-8% by weight - Binder, elastic (e.g. SBR), 8-15% by weight - solvents and / or dispersants, 20-30% by weight The paste contains the ingredients, the percentages of which total 100% by weight.

[0030] Preferably, the immediately preceding features a. to c. and e. to g. are implemented in combination. In a further preferred embodiment, features g. and h. are implemented in combination. Particularly preferably, the immediately preceding features a. to j. are implemented in combination.

[0031] The elastic electrode binder has the function of fixing the metal oxide particles contained in the positive electrode relative to each other and at the same time giving the positive electrode some flexibility. However, the proportion of elastic electrode binder must not exceed the maximum proportion mentioned above, since otherwise there is a risk that the metal oxide particles will no longer be in contact with each other, at least in part. To prevent this, a conductive material is added.

[0032] A high percentage of metal oxide in the positive electrode increases the capacity of the battery. However, for current carrying capacity, the percentage of conductive material is more important than the total percentage of metal oxide. Particularly preferably, the electrode binder in the negative electrode is SBR.

[0033] The conductive material is particularly preferably contained in the paste for producing the negative electrode in a proportion of 5 to 8% by weight.

[0034] As an alternative to the preferably used carboxymethylcellulose, the mineral powders described above for the electrolyte pastes, having an average particle size (d50) of <500 nm, preferably <200 nm, in particular the amorphous silicon dioxide mentioned above, could also be used as additives for adjusting the viscosity in the case of pastes for the positive electrode.

[0035] Process Variations In a first particularly preferred embodiment, the method according to the invention is characterized by the following steps a. to d.: a. A first layer of electrolyte paste is applied, in particular printed, onto either the negative or positive electrode, particularly preferably having a thickness of 30 to 70 μm. b. A separator is applied to the first layer of electrolyte paste. c. A second layer of electrolyte paste is applied, in particular printed, to the separator, particularly preferably having a thickness of 30 to 70 μm. d. A stack of layers is formed and the electrodes not selected in step a. are contacted with a second layer of electrolyte paste. In a second particularly preferred embodiment, the method is characterized by the following steps a. to c.: a. A layer of electrolyte paste is applied, in particular by printing, to each of the negative and positive electrodes, particularly preferably having a thickness of 30 to 70 μm. b. A separator is applied to one of the layers of electrolyte paste so that one side of the separator is in contact with the layer of electrolyte paste. c. A stack of layers is formed and the other side of the separator is contacted with the other of the layers of electrolyte paste. In the stack of layers thus produced, one of the layers of electrolyte paste is necessarily located between the electrode and the separator, or in other words, the separator of the stack of layers thus produced comprises a boundary layer of mineral particles on both sides.

[0036] In particularly preferred embodiments, the method according to the invention is characterized by at least one of the following additional features a. to f.: a. the electrodes and at least one electrolyte layer are formed by a printing process, in particular by a screen printing process; b. The negative electrode is formed with an average thickness within the range of 30 μm to 150 μm. c. The positive electrode is formed with an average thickness within the range of 13 μm to 350 μm. d. At least one electrolyte layer is formed with an average thickness in the range of 10 to 100 μm, preferably 30 to 70 μm. e. At least one electrolyte layer is applied to the negative and / or positive electrode while it is still at least wet ("wet-on-wet application"). f. A separator is placed over one of the formed electrolyte layers while it is still at least wet.

[0037] In a further preferred embodiment, features e and f are realized in combination. It is particularly preferred that features a to f are realized in combination.

[0038] The paste is therefore preferably printed. In order to avoid problems during printing, in a particularly preferred embodiment the printing pastes all contain particulate components with a particle size of 50 μm or less.

[0039] As mentioned above, the electrical conductors are preferably coated with an electrically conductive layer of carbon before the electrodes are applied to protect the conductors from direct contact with the electrolyte. A layer of carbon can also be printed on.

[0040] The electrolyte paste is preferably used in combination with a microporous polyolefin film (e.g. PE) having a thickness in the range of 60-120 μm and a porosity of 35-60%. Preferably, according to the above-mentioned first or second particularly preferred embodiment, a layer of electrolyte paste is formed on the electrodes and / or separators, in particular having a thickness in the specified range, particularly preferably having a thickness of about 50 μm each. The anode is preferably printed as a layer having a thickness of 30 μm to 150 μm, in particular having a thickness of 70 μm. The positive electrode is preferably printed as a layer having a thickness of 180-350 μm, in particular having a thickness of 280 μm.

[0041] As mentioned above, in the method according to the invention, a stack of layers with a continuous negative electrode / separator / positive electrode is formed. This can be preferably done by printing the electrodes of the battery next to each other on the same electrically non-conductive substrate, i.e. in a coplanar arrangement, and folding the substrate or bending it in such a way that the electrodes and the associated separators are superimposed. After folding, the substrate surrounds the resulting stack of layers on at least three sides. The remaining sides can be welded and / or glued to form a closed housing.

[0042] The substrate can be of almost any design. Ideally, the surface must not have any electrically conductive properties, so that short circuits or leakage currents can be made impossible when the conductors of the battery according to the invention are printed directly onto the substrate. For example, the substrate can be a plastic-based label. A foil made of, for example, polyolefin or polyethylene terephthalate, with an adhesive surface on one side where it can be fixed to the product, would be suitable. The electrical conductors of the battery and its other functional parts can be applied to the other side.

[0043] Electrical conductor The electrical conductors can be metal structures formed, for example, by deposition from a solution, by deposition from the gas phase (for example by PVD methods such as sputtering) or by a printing process. It is also possible to form the conductors from a closed metal layer by an etching process in which the metal layer is removed in the unmasked areas.

[0044] In a particularly preferred embodiment, the method is characterized by the following additional feature a: a. The electrical conductor is a conductive path made of metal particles, in particular silver particles or silver alloy particles. Such conductive paths can be easily produced using printing processes: printable conductive pastes with silver particles to produce electrical conductors are conventional and freely available in the industry.

[0045] In a particularly preferred embodiment, the method according to the invention necessarily has the following features: a. The electrical conductor comprises an electrically conductive metal layer. b. The electrical conductor comprises, in at least some areas, an electrically conductive layer of carbon disposed between the metal layer and the electrode, which makes direct contact between the metal layer and the liquid electrolyte difficult or even prevents it.

[0046] The electrically conductive layer of carbon serves to protect the electrical conductor. In particular, if the conductor contains silver particles, there is a risk that the silver will dissolve in the electrolyte, leading to a weakening or even destruction of the conductive path. The carbon layer can protect the conductor made of silver from direct contact with the electrolyte. Preferably, the electrically conductive layer of carbon is applied to have a thickness in the range of 5 μm to 30 μm, in particular in the range of 10 μm to 20 μm. In some preferred embodiments, the carbon layer is subjected to a heat treatment after application, which can increase its impermeability.

[0047] Paste Set The set according to the invention is particularly suitable for use in the method for manufacturing a zinc-manganese dioxide battery described above. It necessarily comprises the following components: a. A paste for making a negative electrode, comprising the following components: - Zinc powder (mercury free) - Electrode binder - Solvents and / or dispersants Including, paste, and b. A paste for making a positive electrode, comprising the following components: - Manganese dioxide - Conductive materials to improve electrical conductivity - Electrode binder - Solvents and / or dispersants Including, paste, and c. A paste for preparing an electrolyte layer, comprising the following components: at least one water-soluble chloride-containing salt, preferably zinc chloride and / or ammonium chloride; - Mineral particles - Solvents and / or dispersants Including, paste.

[0048] With regard to the preferred properties of the three pastes, in order to avoid repetition, reference is made to the above-mentioned description of the method according to the invention. Particularly preferably, the set according to the invention comprises a separator as a further component in order to produce a zinc-manganese dioxide battery. With regard to the preferred properties of the separator, reference is likewise made to the above-mentioned description of the method according to the invention.

[0049] Zinc-manganese dioxide cells and zinc-manganese dioxide batteries According to the subject matter underlying the invention, the battery according to the invention is preferably used to supply a pulsed current load with a peak current of ≧400 mA. It can therefore supply electrical energy, inter alia, to mobile radio chips operating according to the LTE standard. In principle, however, it is also suitable for other applications.

[0050] The zinc-manganese dioxide battery according to the present invention can be produced by the above-mentioned method. It necessarily has the following characteristics a. to f.: a. it comprises a first electrical conductor on an electrically non-conductive substrate, and a second electrical conductor on an electrically non-conductive substrate; b. it comprises a layered negative electrode directly over a first electrical conductor, and a layered positive electrode directly over a second electrical conductor; c. it comprises a layered separator; Where: d. the electrodes and separators are in the form of a stack of layers having a series of negative electrode / separator / positive electrode, the negative electrode and separator and the positive electrode and separator, respectively, being connected to each other via a connecting portion; Where: e. the electrodes and the separator are preferably impregnated with an aqueous chloride solution, in particular preferably with an aqueous zinc chloride solution and / or preferably with an aqueous ammonium chloride solution; and where f. The interface between the electrode and the separator is characterized by mineral particles which form a boundary layer therebetween which is permeable to the electrolyte.

[0051] Because the boundary layer helps to electrically isolate the positive and negative electrodes from each other due to its content of mineral filler particles, it can also be considered a component of the separator. In a particularly preferred embodiment, the layered separator of a zinc-manganese dioxide cell according to the invention comprises two such boundary layers, i.e., one on each of its sides.

[0052] Particularly preferably, the zinc-manganese dioxide battery is characterized by at least one of the following features a. and b.: a. The negative electrode of the battery contains the following components in the following proportions: - Zinc powder (mercury-free), 81-93% by weight - Additives for viscosity adjustment, 1-7% by weight - Electrode binder, 6-13% by weight Contains. b. The positive electrode of the battery contains the following components in the following proportions: - Manganese dioxide, 62-82% by weight - Conductive materials, 5-35% by weight - Additives for viscosity adjustment, 2-10% by weight - Electrode binder, 6-13% by weight Contains. The immediately preceding features a. and b. are preferably realised in combination.

[0053] With regard to the preferred properties of the listed components of the battery, i.e. for example the electrical conductors or the mineral particles forming the boundary layer, reference is made to the above description of the method according to the invention in order to avoid repetition.

[0054] It is particularly preferred that the battery according to the invention is characterized by at least one of the following additional features a. to c.: The electrodes are rectangular or in the form of strips. b.An electrode is - a length in the range of 1 cm to 25, preferably 5 cm to 20 cm; and - a width in the range of 0.5 to 10 cm, preferably 1 cm to 5 cm; Having. c. The electrical conductor on the electrically non-conductive substrate has a thickness in the range of 2 μm to 250 μm, preferably 2 μm to 100 μm, more preferably 2 μm to 25 μm, and even more preferably 5 μm to 10 μm. Preferably, the immediately preceding features a. to c. are implemented in combination with each other.

[0055] The positive and negative electrodes of the battery according to the invention each have a particularly preferred thickness in the range of 10 μm to 250 μm. The positive electrode is usually somewhat thicker than the negative electrode, since the latter often has a higher energy density. Depending on the application, it may therefore be preferable to form the negative electrode as a layer having a thickness of 30 μm to 150 μm and the positive electrode as a layer having a thickness of 180 to 350 μm. By adjusting the thickness, the capacitance of the positive and negative electrodes can be balanced. In this regard, the positive electrode is preferably made larger than the negative electrode.

[0056] The invention also includes a battery comprising two or more zinc-manganese dioxide cells according to the invention. Particularly preferably, the battery comprises two, three or four series-connected zinc-manganese dioxide cells according to the invention.

[0057] The cell according to the invention and the battery according to the invention are preferably characterized by at least one of the following features a. and b.: It comprises a housing that surrounds the electrodes of the cell or battery, the first and second substrates being part of the housing. b. The first and second substrates are foils or components of a foil. Again, the immediately preceding features a. and b. are preferably realised in combination with each other.

[0058] The battery according to the invention, including the housing, preferably has a maximum thickness in the range of a few millimeters, particularly preferably in the range of 0.5 mm to 5 mm, more preferably in the range of 1 mm to 3 mm. Its other dimensions depend on the number of electrically interconnected individual cells and their dimensions. For example, a battery with four series-connected individual cells may have a length of 5 to 20 cm and a width of 4 to 18 cm.

[0059] Particularly preferably, the cell according to the invention or the battery according to the invention can be placed or produced on a plastic-based label, in particular an adhesive label made of plastic. For example, the first or second substrate can be a foil with an adhesive layer on one of its sides. The label can be adhered to any product or package. If necessary, electronic applications such as mobile phone chips, which are supplied with electrical energy by the cell according to the invention or the battery according to the invention, can also be placed on the label. Particularly for this application, it is necessary for the electrodes to have a high degree of flexibility, which can be ensured by the proportion of elastic electrode binder.

[0060] As mentioned above, in a preferred embodiment, the electrodes and at least one electrolyte layer of the battery according to the invention are formed by a printing process, in particular by a screen printing process. In a particularly preferred embodiment, the battery according to the invention is therefore a printed battery.

[0061] In this context, a printed battery is to be understood as a battery in which at least the electrodes and the electrolyte layer, and optionally also the electrical conductors, are formed by printing the above-mentioned printing paste onto a substrate, in particular by means of a screen printing process. Preferably, the electrodes and the electrical conductors are printed.

[0062] Further features of the present invention and advantages resulting from the present invention will become apparent from the following examples of embodiments and the drawings, with the help of which the present invention will be explained. The embodiments described below merely serve to explain the present invention and provide a deeper understanding thereof, and should in no way be understood as limiting. [Brief description of the drawings]

[0063] Further advantages and aspects of the invention will become apparent from the claims and from the following description of preferred examples of embodiments of the invention, which are illustrated below with reference to the drawings in which: FIG. [Figure 1] FIG. 1 is a diagram of a preferred embodiment of a method for manufacturing a battery according to the present invention, comprising a total of four electrically interconnected cells according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a battery formed according to the method shown in FIG. [Diagram 3] FIG. 3 shows the results of a pulse test using a battery according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0064] Both the production and construction of a preferred embodiment of a battery 100 according to the present invention having four individual cells electrically connected in series can be described with reference to Figure 1. The manufacturing method includes the following steps:

[0065] (1) A current conductor structure is printed by screen printing on a PET film 106 having a thickness of 200 μm, which serves as a carrier. The PET film 106 is divided into two regions 109a and 109b by a line 109. Among them, the region 109a serves as a first substrate, and the region 109b serves as a second substrate. The current conductor structure includes a first electric conductor 101, a second electric conductor 102, a third electric conductor 103, a fourth electric conductor 104, and a fifth electric conductor 105, where the first and third conductors 101 and 103 are printed on the first substrate 109a. The conductors 102, 104, and 105 are printed on the second substrate 109b. The printing paste used here is a commercially available silver conductive paste. In the area of ​​the electrical conductors 101-105, the PET foil 106 is in each case coated with paste over its entire surface, so that the conductors each form a continuous electrically conducting surface. All electrical conductors are preferably formed as layers having a thickness in the range of 10 μmμm to 100 μm. The result of this step is shown in FIG. 1A. It should be noted here that all layers shown in the drawing are arranged parallel to the drawing plane. This applies equally to the carbon, electrode and electrolyte layers deposited on the conductors.

[0066] (2) In a further step, the current conductor structure is covered with a thin layer of carbon particles. The layer of carbon particles is preferably formed to have a thickness of 12 μm. The printing paste used here is a typical carbon paste of the kind used to form electrical conductive layers and interconnects in electronic devices. In FIG. 1B the result of this step is shown. In order to optimize the coverage of the current conductor structure with the layer of carbon particles, it may be preferable to subject the formed layer to a heat treatment. The temperature that may be applied depends mainly on the thermal stability of the PET foil and must be selected accordingly.

[0067] (3) Next, the negative electrodes 107a, 107b, 107c, and 107d, and the positive electrodes 108a, 108b, 108c, and 108d are printed on the current conductor structure. For this purpose, the first electrical conductor 101 is overprinted in areas with zinc paste to form the negative electrode 107b, and in areas with manganese oxide paste to form the positive electrode 108a. The second electrical conductor 102 is overprinted in some areas with zinc paste to form the negative electrode 107c, and in some areas with manganese oxide paste to form the positive electrode 108b. The third electrical conductor 103 is overprinted in some areas with zinc paste to form the negative electrode 107d, and in some areas with manganese oxide paste to form the positive electrode 108c. The fourth electrical conductor 104 is overprinted in some areas with manganese oxide paste to form the positive electrode 108d. Additionally, the fifth electrical conductor 105 is overprinted in areas with zinc paste to form the negative electrode 107a. The paste has the following composition: Zinc Paste: - Zinc particles 70% by weight - CMC 2% by weight - SBR 6% by weight - Solvents and / or dispersants (water) 22% by weight Manganese oxide paste: - Manganese oxide 60% by weight - Graphite 6% by weight - Zinc chloride 2% by weight - CMC 2% by weight - SBR 5% by weight - Solvents and / or dispersants (water) 25% by weight The result of this step is shown in FIG. 1C.

[0068] The negative electrodes 107a-107d and positive electrodes 108a-108d are each formed as a rectangular strip having a length of 11 cm and a width of 2 cm. The negative electrodes 107a-107d are preferably formed as layers having a thickness of 70 μm here. The positive electrodes 108a-108d are preferably formed as layers having a thickness of 280 μm. More than one printing process may be required to form the positive electrodes 108a-108d.

[0069] Two of the electrodes are electrically connected via each of a first conductor 101, a second conductor 102, and a third conductor 103. Conductor 101 connects positive electrode 108a to negative electrode 107b, conductor 102 connects positive electrode 108b to negative electrode 107c, and conductor 103 connects positive electrode 108c to negative electrode 107d. These electrical connections are the basis for the desired series connection of the four individual cells.

[0070] Conductors 101, 102, and 103, each electrically connecting two electrodes, each form an electrically conductive area on the surface of the respective substrate 109a and 109b that is larger than the area occupied by the electrically connected electrodes 108a and 107b, 108b and 107c, and 108c and 107d on the surface. In one embodiment, the electrically conductive area each includes the area covered by the electrode. Secondly, a gap 110 is formed between each of the electrically connected electrodes, separating the electrodes from each other. The electrically conductive surface also spans this gap 110, so that the cross section of the conductor in the gap between the electrodes is not reduced.

[0071] All this already has a positive effect on the impedance value of the battery 100 according to the invention. The large area contact of the electrodes, and in particular also the connection through the gap 110, ensures an optimal electrical connection of the electrodes and minimizes the electrical resistance.

[0072] Additionally, the fourth and fifth conductors 104 and 105, which are in electrical contact only with electrodes 107a and 108d, form electrically conductive areas on the surface of the respective substrates that are larger than the areas occupied by the respective electrically contacted electrodes on the surface. In one embodiment, the electrically conductive areas each include areas that are covered by the electrodes. On the other hand, the electrically conductive surfaces each include areas that are not covered by the electrode material. These areas can serve as terminals of the battery 100 to draw the combined voltage of its four series-connected individual cells.

[0073] (5) In a further subsequent step, zinc chloride paste is printed onto the negative electrodes 107a-107d and the positive electrodes 108a-108d. For example, electrolyte paste layers 111a-111h each having a thickness of approximately 50 μm are formed. The result of this step is shown in FIG. 1D. Preferably, an electrolyte paste having the following composition is used in this step: - Zinc chloride 35% by weight - Floating agent (silicon dioxide) 3% by weight - Mineral, water-insoluble particles (CaCO3) 15% by weight - Solvents and / or dispersants (water) 47% by weight The actuator and the water-insoluble particles have an electrical insulating effect.

[0074] It is particularly advantageous if a sealing frame 112 surrounding the electrodes is formed, for example with an adhesive compound, before the paste is printed around the individual electrodes. For example, a commercially available solder resist can serve as a starting material for forming the sealing frame 112. Two sealing frames 112 surrounding the electrodes 107a and 108a are shown as an example. If the process is carried out properly, it is advantageous to surround all the electrodes with a sealing frame.

[0075] (6) The electrolyte paste layers 111a-111h are then coated with a plurality of separators, preferably immediately after printing the electrolyte paste layers so that the electrolyte paste layers do not dry out. The PET foil 106 is then folded over along lines 109, thereby forming a fold over the PET foil 106. the negative electrode 107a forms a first stack of layers with one of the separators and with the positive electrode 108a; the negative electrode 107b forms a second stack of layers with one of the separators and with the positive electrode 108b; the negative electrode 107c forms a third stack of layers with one of the separators and with the positive electrode 108c; - The negative electrode 107d forms a fourth stack of layers with one of the separators and with the positive electrode 108d. By folding and final welding and / or gluing, a closed housing can be formed with the stack of layers disposed inside. The result of this step is shown in Figure 2. A microporous polyolefin film with a thickness in the range of 60-120 μm and a porosity (ratio of void volume to total volume) of 35-60% is used as a separator for this purpose.

[0076] The battery 100, shown in cross-section in Figure 2, comprises four individual cells 113, 114, 115, and 116, each having the form of a stack of layers. The battery shown can be produced according to the method shown in Figure 1, where a total of four separators 117a-117d formed as layers are used to form the individual cells. In addition to the separators 117a-117d, the stacks of layers 113-116 each include one of the negative electrodes 107a-107d and one of the positive electrodes 108a-108d.

[0077] In more detail: The stack of layers 113 includes electrical conductors 101 and 105, which include layers 101a and 105a of carbon particles that protect them from contact with the electrolyte. The positive electrode 108a is deposited directly on the layer 101a, and the negative electrode 107a is deposited directly on the layer 105a. Between the electrodes 107a and 108a is a separator 117a, surrounded by electrolyte paste layers 111a and 111b. The electrolyte layers 111a and 111b, by virtue of their content of electrically non-conductive mineral particles, help to electrically isolate the positive electrode 108a and the negative electrode 107a from each other, so that they can be considered as components of the separator 117a. In any case, the mineral particles form a boundary layer between the electrodes and the separator, which is, however, permeable to zinc chloride dissolved in water.

[0078] The stack of layers 114 includes electrical conductors 101 and 102, which include layers 101a and 102a of carbon particles that protect them from contact with the electrolyte. The positive electrode 108b is deposited directly on the layer 102a, and the negative electrode 107b is deposited directly on the layer 101a. Between the electrodes 107b and 108b is a separator 117b, surrounded by electrolyte layers 111c and 111d. The electrolyte layers 111c and 111d, due to their content of electrically non-conductive mineral components, help to electrically isolate the positive electrode 108b and the negative electrode 107b from each other, so they can be considered as components of the separator 117b. In any case, the mineral particles form a boundary layer between the electrodes and the separator, which is, however, permeable to zinc chloride dissolved in water.

[0079] The stack of layers 115 includes electrical conductors 102 and 103, which include layers 102a and 103a of carbon particles that protect them from contact with the electrolyte. The positive electrode 108c is deposited directly on the layer 103a, and the negative electrode 107c is deposited directly on the layer 102a. Between the electrodes 107c and 108c is a separator 117c, surrounded by electrolyte layers 111e and 111f. The electrolyte layers 111e and 111f can be considered as components of the separator 117c, because they help to electrically isolate the positive electrode 108c and the negative electrode 107c from each other due to their content of electrically non-conductive mineral components. In any case, the mineral particles form a boundary layer between the electrodes and the separator, which is, however, permeable to zinc chloride dissolved in water.

[0080] The stack of layers 116 includes electrical conductors 103 and 104, which include layers 103a and 104a of carbon particles that protect them from contact with the electrolyte. The positive electrode 108d is deposited directly on the layer 104a, and the negative electrode 107d is deposited directly on the layer 103a. Between the electrodes 107d and 108d is a separator 117d, surrounded by electrolyte layers 111g and 111h. The electrolyte layers 111g and 111h, due to their content of electrically non-conductive mineral components, help to electrically isolate the positive electrode 108d and the negative electrode 107d from each other, so they can be considered as components of the separator 117d. In any case, the mineral particles form a boundary layer between the electrodes and the separator, which is, however, permeable to zinc chloride dissolved in water.

[0081] The first conductor 101 and the third conductor 103 are arranged at a distance from each other on the surface of the first substrate 109a facing the second substrate 109b, while the second conductor 102, the fourth conductor 104, and the fifth conductor 105 are arranged at a distance from each other on the surface of the second substrate 109b facing the first substrate 109a.

[0082] The four individual cells 113, 114, 115, and 116 are electrically connected in series such that their voltages are summed. For this purpose, the opposite polarity electrodes of the single cells are electrically connected via a first conductor 101, a second conductor 102, and a third conductor 103. The conductor electrodes have opposite polarity, and the first conductor is in electrical contact with the electrodes of a fourth single cell, the electrodes electrically connected by this conductor also have opposite polarity. As mentioned above, the areas of the conductors 104 and 105 that are not covered by the electrode material can serve as the terminals of the battery 100 to draw the summed voltage of its four series-connected individual cells 113-116.

[0083] Because the individual cells 113-116 described herein are based on zinc-manganese dioxide as an electrochemical system, each of the cells provides a nominal voltage of about 1.5 volts. Thus, the battery 100 has the capability of providing a nominal voltage of about 6 volts.

[0084] As a result of the above-mentioned folding and final welding and / or gluing along lines 117, the battery 110 according to the invention has a closed housing 118 within which the stack of layers 113-116 is disposed. The areas of the conductors 104 and 105 that are not covered by electrode material can be led out of the housing so that the voltage of the battery 100 can be drawn from the outside.

[0085] It is important for the impedance characteristics of the battery 100 according to the invention that the layered components of the individual cells 113-116, which are in direct contact within the stack of layers, are in contact with each other over as large an area as possible.

[0086] First, in order to optimize the impedance, it is necessary to provide contact between the electrodes 107a and 108a and the electrical conductors 101 and 105 over as large an area as possible. As described above, the conductors 101 and 105 form continuous electrically conductive surfaces on the substrates 109a and 109b, respectively, as shown in Figures 1A and 1B. The electrically conductive surfaces formed by the conductor 101 and the electrode 108a deposited thereon approximately overlap in a viewing direction perpendicular to the electrodes 108a and the conductor 101, in the overlay area where a straight line perpendicular to the electrode 108a intersects both the electrode and the conductor 101. In certain cases, this overlay area is strictly the area of ​​the electrode 108a. The electrode 108a is therefore in contact with the electrical conductor 101 over its entire surface. The same is equally true in the case of the contact between the electrode 107a and the conductor 105. Here too, there is a full surface contact.

[0087] Furthermore, the connection of the electrodes 107a and 108a to the separator 117a is important. As mentioned above, the separator 117a is in contact with the electrodes 107a and 108a through the electrolyte layers 111a and 111b or boundary layers formed from mineral particles, which in this example can be considered as part of the separator 117a. One side of the separator has a first contact surface to the positive electrode 108a and the other side parallel to it has a second contact surface to the negative electrode 107a. Preferably, the contact surfaces overlap each other in a viewing direction perpendicular to the separator within an overlay area defined by a straight line perpendicular to the separator that intersects both contact surfaces.

[0088] The size of this overlay area corresponds closely to the size of the electrodes 107a and 108a, since the electrodes 107a and 108a have the same surface dimensions and are not offset relative to one another in the stack, and therefore the electrodes 107a and 108a are in full contact not only with the conductors 101 and 105, but also with the separators, or electrolyte layers 111a and 111b of the separators.

[0089] The pulse test results shown in Figure 3 were conducted using a battery designed according to Figure 2 with four individual cells electrically connected in series. The electrodes of the four cells were each approximately 22 cm above their respective substrates. 2 The individual cells were electrically connected in series to provide a nominal voltage of 6V. In practice, the open circuit voltage was about 6.4 volts and the end-of-discharge voltage was about 3.1 volts. Prior to the measurements, the batteries were stored at 45° for a period of one month to artificially simulate aging. Nevertheless, the batteries delivered a total of 118 TX pulses. The unused battery delivered over 400 Tx pulses in the load test, making it ideally suited to power an LTE chip.

Claims

1. 1. A method for producing a zinc-manganese dioxide battery, comprising the steps of: a. applying a first electrical conductor to an electrically non-conductive substrate and a second electrical conductor to an electrically non-conductive substrate; b. applying a layered negative electrode directly onto the first electrical conductor and a layered positive electrode directly onto the second electrical conductor; c. providing a layered separator; d. applying at least one electrolyte layer to the layered negative electrode, and / or to the layered positive electrode, and / or to the layered separator; e. forming a stack of layers having the continuous anode / separator / cathode; Including, f. The negative electrode comprises the following components: - Zinc powder (mercury free) - Electrode binder - Solvents and / or dispersants The paste is formed from g. The positive electrode comprises the following components: - Manganese dioxide - Conductive materials to improve electrical conductivity - Electrode binder - Solvents and / or dispersants The paste is formed from h. said at least one electrolyte layer comprising the following components: at least one water-soluble chloride-containing salt; - Mineral particles - Solvents and / or dispersants The paste is formed from A method, wherein the proportion of said mineral particles in said paste is at least 5% by weight and at most 60% by weight.

2. Additional features include: a. The separator is a porous plastic film or a porous nonwoven fabric; b. the separator has a thickness in the range of 60 to 120 μm; c. the separator has a porosity (ratio of void volume to total volume) in the range of 35-60%; d. The separator is made of a polyolefin; The method of claim 1 , comprising at least one of:

3. Additional features include: a. the mineral particles are selected from the group consisting of ceramic particles, salt particles that are nearly or completely insoluble in water, glass particles, and particles of natural minerals and rocks; b. CaCO 3 The particles are used as mineral particles; c. the mineral particles have a d50 value in the range of 0.8 μm to 40 μm; d. the paste for producing the at least one electrolyte layer is substantially free of mineral particles having a particle size >80 μm; e. the paste for producing the at least one electrolyte layer comprises at least one additive for adjusting its viscosity; f. As an additive for adjusting viscosity, the paste contains a mineral powder having an average particle size (d50) of <500 nm; g. Water is used as a solvent and / or dispersant; h. the proportion of said at least one water-soluble chloride-containing salt in said paste is at least 25% by weight and at most 50% by weight; i. said paste for producing said at least one electrolyte layer comprises the following components in the following proportions: - 30 to 40% by weight of said at least one water-soluble chloride-containing salt - Additives for adjusting viscosity, 2-4% by weight mineral particles, 10-30% by weight - solvents and / or dispersants, 40 to 55% by weight wherein the percentages of the components of the paste add up to 100% by weight; The method of claim 1 , comprising at least one of:

4. Additional features include: a. the paste for preparing the negative electrode contains the zinc powder in a proportion of at least 50% by weight; b. the zinc powder is characterized by a d50 value in the range of 20 μm to 40 μm; c) the paste for producing the negative electrode contains at least one additive for adjusting its viscosity; d. the paste contains carboxymethyl cellulose as an additive for adjusting viscosity; e. the paste for making the negative electrode contains the electrode binder in an amount of at least 1 wt.%; f. the paste for producing the negative electrode comprises an electrode binder having elastic properties; g. Water is used as a solvent and / or dispersant; h. The paste for preparing the negative electrode contains the following components in the following proportions: Zinc powder (mercury-free), 65-79% by weight - Additives for adjusting viscosity, 1 to 5% by weight - Binder, elastic, 5-10% by weight - solvents and / or dispersants, 15 to 20% by weight wherein the percentages of the components of the paste add up to 100% by weight; The method of claim 1 , comprising at least one of:

5. Additional features include: a. the paste for preparing the positive electrode contains the manganese dioxide in a proportion of at least 50% by weight; b. the manganese dioxide is present in particulate form and is characterized by a d50 value in the range of 20 μm to 50 μm; c. the paste for producing the positive electrode includes at least one additive for adjusting its viscosity; d. the paste contains carboxymethyl cellulose as an additive for adjusting viscosity; e. the paste for preparing the positive electrode comprises the electrode binder in a proportion of at least 5% by weight; f. the paste for producing the positive electrode comprises an electrode binder having elastic properties; g. the paste for producing the positive electrode contains the conductive material in a ratio of 5% to 35% by weight; h) the positive electrode fabrication paste comprises at least one conductive material selected from the group consisting of activated carbon, activated carbon fiber, carbide-derived carbon, carbon aerogel, graphite, graphene, and carbon nanotubes (CNTs); i. Water is used as a solvent and / or dispersant; j. The paste for preparing the positive electrode contains the following components in the following proportions: manganese dioxide, 50-70% by weight Conductive material, 3-30% by weight - Additives for adjusting viscosity, 2 to 8% by weight - Electrode binder, elastic, 8-15% by weight - solvents and / or dispersants, 20 to 30% by weight wherein the percentages of the components of the paste add up to 100% by weight; The method of claim 1 , comprising at least one of:

6. Additional features include: a. the electrodes and the at least one electrolyte layer are formed by a printing process; b. The negative electrode is formed with an average thickness in the range of 30 μm to 150 μm; c. The positive electrode is formed with an average thickness in the range of 13 μm to 350 μm; d. the at least one electrolyte layer is formed with an average thickness in the range of 10 to 100 μm; e. the at least one electrolyte layer is applied to the negative electrode and / or the positive electrode while it is still at least wet ("wet-on-wet application"); f. placing said separator over one of said formed electrolyte layers while it is still at least wet; The method of claim 1 , comprising at least one of:

7. A set for the production of zinc-manganese dioxide batteries, comprising the following components: a. A paste for making a negative electrode, comprising the following components: - Zinc powder (mercury free) - Electrode binder - Solvents and / or dispersants A paste comprising: b. A paste for making a positive electrode, comprising the following components: - Manganese dioxide - Conductive materials to improve electrical conductivity - Electrode binder - Solvents and / or dispersants A paste comprising: c. A paste for preparing an electrolyte layer, comprising the following components: at least one water-soluble chloride-containing salt; - Mineral particles - Solvents and / or dispersants A paste comprising: A set having:

8. As a further component, a separator for a zinc-manganese dioxide battery, said separator having the following properties: a. The separator is a porous plastic film or a porous nonwoven fabric; b. the separator has a thickness in the range of 60 to 120 μm; c. the separator has a porosity (ratio of void volume to total volume) in the range of 35-60%; d. The separator is made of a polyolefin; The set of claim 7, comprising:

9. A zinc-manganese dioxide battery producible according to the method of any one of claims 1 to 6, having the following characteristics: a. it comprises a first electrical conductor on an electrically non-conductive substrate, and a second electrical conductor on an electrically non-conductive substrate; b. it comprises a layered negative electrode directly over said first electrical conductor, and a layered positive electrode directly over said second electrical conductor; c. it comprises a layered separator; Where: d) the electrodes and separator are in the form of a stack of layers with the continuous negative electrode / separator / positive electrode, the negative electrode and separator, and the positive electrode and separator, respectively, being connected to each other via a connecting portion; Where: e. the electrodes and the separator are immersed in a chloride solution; and where f. the interface between the electrode and the separator is characterized by mineral particles that form a boundary layer that is permeable to the electrolyte; A zinc-manganese dioxide battery comprising:

10. Features: a. the negative electrode of the battery comprises the following components in the following proportions: Zinc powder (mercury-free), 81-93% by weight - Additives for adjusting viscosity, 1 to 7% by weight - electrode binder, 6-13% by weight containing, b. The positive electrode of the battery comprises the following components in the following proportions: manganese dioxide, 62-82% by weight Conductive material, 5-35% by weight - Additives for adjusting viscosity, 2-10% by weight - electrode binder, 6-13% by weight containing, 10. The zinc-manganese dioxide battery of claim 9, characterized in that:

11. Features: a. the mineral particles are selected from the group consisting of ceramic particles, salt particles that are nearly or completely insoluble in water, glass particles, and particles of natural minerals and rocks; b. CaCO 3 The particles are used as mineral particles; c. the mineral particles have a d50 value in the range of 0.8 μm to 40 μm; d. the boundary layer comprises mineral particles having an average particle size (d50) of <500 nm; 10. The zinc-manganese dioxide battery of claim 9, characterized in that: